PERAN DINAS SOSIAL KOTA PEKANBARU UNTUK MENDUKUNG PROGRAM PEMERINTAH MENGENAI ASISTENSI SOSIAL LANJUT USIA TERLANTAR (ASLUT) TAHUN 2017-2018 - Iqbal Kurniawan Syah; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Keywords: Role, Neglected Elderly, ASLUT Article 27 paragraph (2) of the 1945 Constitution states that "every citizen has the right to work and livelihood that is appropriate for humanity". This means that every Indonesian citizen has the right to receive assistance from the government to get a decent living, especially for groups of people with Social Welfare Problems (PMKS), one of which is neglected elderly. Based on Minister of Social Affairs Regulation Number 12 of 2013 concerning the ASLUT Program, the government is obliged to provide social security to help displaced elderly people in fulfilling some of their basic needs. The government in this case the Office of Social Affairs has a role and aims to support the government program regarding Neglected Elderly Social Assistance (ASLUT) based on the principle of assistance (medebewind). Therefore the author formulates the problem, namely: why the role of the Pekanbaru City Social Service to support the Government's program regarding Neglected Elderly Social Assistance (ASLUT) in 2017-2018 is not optimal. The purpose of this study was to: (1) find out the role of the Pekanbaru City Social Service to support the government program regarding the Assistance for Displaced Ages (ASLUT) for 2017-2018. (2) knowing the inhibiting factors for the role of the Social Service Office to support the government program regarding the Assistance for Neglected Elderly (ASLUT) for 2017-2018. This study uses a qualitative research method with a type of descriptive research, which can be interpreted as a problem-solving process that is investigated by describing the state of the research subject based on the facts that appear during the research which then proceed based on existing theories. The research was carried out at the Pekanbaru City Social Service. The selection of informants is done by purposive technique. Data collection techniques used during conducting research are by interview and documentation. The results of this study indicate that the role of the Social Service Office in Pekanbaru City to support the Government's program regarding ASLUT has not played an optimal role. This is indicated by the problem of data collection of prospective ASLUT recipients who do not have self-identities such as ID cards and often found ID cards that are not valid. In addition to data collection, the second obstacle encountered in the field is the issue of issuing ASLUT cards and ASLUT recipients often experiencing delays.